2008
DOI: 10.1002/humu.20751
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mapping of the 8p23.1 beta-defensin cluster reveals strictly concordant copy number variation of all genes

Abstract: One unexpected feature of the human genome is the high structural variability across individuals. Frequently, large regions of the genome show structural polymorphisms and many vary in their abundance. However, accurate methods for the characterization and typing of such copy number variations (CNV) are needed. The defensin cluster at the human region 8p23.1 is one of the best studied CNV regions due to its potential clinical relevance for innate immunity, inflammation, and cancer. The region can be divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 30 publications
8
75
0
Order By: Relevance
“…Consistent with previous data (18)(19)(20)(21), copy number among the parents of these 26 families varied between 2 and 7, with a modal copy number of 4 and a mean of 4.58. We observed that at least 24 offspring inherited recombinant haplotypes in which parental copies of the ␤-defensin repeat had been reassorted.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous data (18)(19)(20)(21), copy number among the parents of these 26 families varied between 2 and 7, with a modal copy number of 4 and a mean of 4.58. We observed that at least 24 offspring inherited recombinant haplotypes in which parental copies of the ␤-defensin repeat had been reassorted.…”
Section: Resultssupporting
confidence: 91%
“…Although the copy-variable ␤-defensins have generally been treated as outside the inverted segment (28,29), it is evident that at least at the distal locus they are located between complex nested series of repeat sequences (REPD) (17,26,29,30), of which different elements may sponsor a variety of exchanges, including recombination between inverted repeats at REPP to mediate a change in inversion status. Despite the dynamic nature of the defensin repeats, it is clear that there are few if any repeats of variant gene composition; measurements of copy number within the defensin CNV have shown that the copy numbers of all genes in the repeat vary coordinately (18,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within DEFA, the CNV unit of 19 kb encompasses DEFA1A3 and the pseudogene DEFTP. [10][11][12][13][14] However, the 200 kb DEFB varies en bloc in its copy number (CN). 11 Individuals carrying 2-12 copies per diploid genome were found.…”
Section: Introductionmentioning
confidence: 99%
“…6 The human b-defensin genes (DEFB) are clustered on chromosome 8p23.1 and show considerable variations in copy number except for DEFB1, which has only two copies per diploid genome. 7 This makes DEFB1 accessible to straightforward association analysis of potential genetic susceptibility variants. Consistent with all human epithelial tissues tested to date, including intestinal mucosa, 8 the urogenital tract, 9 and airway epithelia, 10 DEFB1 is constitutively expressed in the gingival epithelial tissues.…”
Section: Introductionmentioning
confidence: 99%